A class of proportional-integral siding mode control with application to active suspension system - Ab Ghani, Mohd Ruddin (Elsevier, 2004)
The purpose of this paper is to present a new robust strategy in controlling the active suspension system. The strategy utilized the proportional-integral sliding mode control scheme. A quarter-car model is used in this study and the performance of the controller is compared to the linear quadratic regulator and with the existing passive suspension system. A simulation study is performed to prove the effectiveness and robustness of the control approach.